Yield, physiology and quality of yellow melon grown with biofertilizer - Emerson Wilberto Silva Leite; Marlon da Silva Garrido; Welson Lima Simoes; Alessandra Monteiro Salviano; Alessandro Carlos Mesquita (Pesquisa Agropecuária Tropical, 2023)
An efficient organic cultivation can be a viable strategy to enhance the sustainability of the melon production chain. This study aimed to assess the physiological and productive responses, as well as the post-harvest quality, of melon fruits, as a function of biofertilizer doses. The experiment followed a randomized blocks design, in a split-plot arrangement, with four replications. The treatments included six biofertilizer doses (0, 1, 2, 3, 4 and 5 L plant-1) as subplots and two melon hybrids (AC 154 and Royal Amália) as plots. The use of 3 L plant-1 cycle-1 of the biofertilizer increased the sugar content in the leaf tissue, improved the photosynthetic efficiency, enhanced the biochemical variables and provided higher yields, in addition to improving the fruit post-harvest quality of the tested hybrids.